Nuclear and particle physics - Amsler, C., 1947- (IOP (Series). Release 2., 2015)
This book provides an introductory course on Nuclear and Particle physics for undergraduate and early-graduate students, which the author has taught for several years at the University of Zurich. It contains fundamentals on both nuclear physics and particle physics. Emphasis is given to the discovery and history of developments in the field, and is experimentally/phenomenologically oriented. It contains detailed derivations of formulae such as 2- 3 body phase space, the Weinberg-Salam model, and neutrino scattering. Originally published in German as 'Kern- und Teilchenphysik', several sections have been added to this new English version to cover very modern topics, including updates on neutrinos, the Higgs boson, the top quark and bottom quark physics.